Penerapan Metode Guided Inquiry Untuk Meningkatkan Kemampuan Eksplorasi Dalam Pembelajaran Seni Budaya Dan Prakarya Pada Siswa Kelas IV SDN 193 Tanuntung Kab. Bulukumba - Rezky Aulya Yusuf; Rosleny Babo; Roslyn Roslyn (Mathematics Education Study Program, 2025)
The main problem in this study is how to apply the Guided Inquiry method as a learning method that can improve the exploration ability and learning outcomes of fourth grade students of SDN 193 Tanuntung, Bulukumba Regency. This study aims to improve the exploration ability and learning outcomes of fourth grade students of SDN 193 Tanuntung, Bulukumba Regency. This type of research is classroom action research (Class Action Research) consisting of two cycles where each cycle is carried out in two meetings. The research procedure includes planning, implementing actions, observation, and reflection. The subjects in this study were 18 fourth grade students of SDN 193 Tanuntung, Bulukumba Regency. The results of the study showed that in cycle I, only 4 students or 22.2% of the 18 students were completed individually and met the minimum completeness criteria (KKM). While in cycle II, the number of learning completeness from 18 students was 18 students who completed or 100%. Thus, it is known that the difference in students who completed their learning outcomes classically from cycle I to cycle II is 14 students or 77.8% in the very high category. Based on the results of the study above, it can be concluded that the exploration ability and learning outcomes in the learning of Arts and Crafts of grade IV students of SDN 193 Tanuntung, Bulukumba Regency. have increased.